The moderating effect of digitalization on the collapse of bank performance during the COVID-19 pandemic: The case of GCC banks - Guermazi, Imene; Chabchoub, Mohamed; Smaoui, Aida (International Journal of Innovative Research and Scientific Studies, 2025)
This paper focuses on the moderating impact of digitalization on the performance breakdown of the GCC banking sector during the outbreak of COVID-19. We observe 57 banks in Saudi Arabia, Kuwait, the UAE, Bahrain, Qatar, and Jordan during the period from 2004 to 2020. We use the fixed effect model, the random effect model, and the Hausman test to adopt the most suitable model for the sample study. We regress the return on assets on CAMEL variables measuring bank soundness and a dummy variable proxying the outbreak period. We test the moderating effects of efficiency, growth, and digitalization using cross-variables. Our findings show that bank performance in GCC countries depends significantly on capital adequacy and efficiency. Furthermore, we find evidence that the pandemic has decreased bank performance. This detrimental effect is moderated by the degree of digitalization, investment growth, and bank efficiency. Our findings should help policymakers assess feedback on their investment agendas, specifically their commitment to enhancing economic growth and resilience through the promotion of digitalization. These implications for this specific case study of GCC countries would also be beneficial not only for other emerging economies in Asia but beyond the Asian continent.